2007
DOI: 10.1016/j.freeradbiomed.2007.04.028
|View full text |Cite
|
Sign up to set email alerts
|

6-Hydroxydopamine induces mitochondrial ERK activation

Abstract: Reactive oxygen species (ROS) are implicated in 6-hydroxydopamine (6-OHDA) injury to catecholaminergic neurons; however, the mechanism(s) are unclear. In addition to ROS generated during autoxidation, 6-OHDA may initiate secondary cellular sources of ROS that contribute to toxicity. Using a neuronal cell line, we found that catalytic metalloporphyrin antioxidants conferred protection if added 1 hour after exposure to 6-OHDA, whereas the hydrogen peroxide scavenger catalase failed to protect if added more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 83 publications
0
66
0
1
Order By: Relevance
“…24 Early transient ERK1/2 activation accompanied by nuclear translocation is associated with enhanced neuronal survival, 21,22,54,55 while cytoplasmic ERK1/2 without evidence of nuclear localization is typical of degenerating neurons of Alzheimer's disease, 50 and in PD and related models. 25,35 While it is not possible to tell from human autopsy studies whether ERK1/2 regulates mitochondrial turnover or is passively localized to mitochondria and AVs, the current study indicates that activity level-dependent localization of ERK2 to mitochondria is sufficient to induce mitophagy. Moreover, dominant interfering ERK2-KD expression and the MEK inhibitor U0126 prevented both generation and colocalization of ERK2 granules with mitochondria, suppressing 6-OHDA induced mitophagy ( Fig.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…24 Early transient ERK1/2 activation accompanied by nuclear translocation is associated with enhanced neuronal survival, 21,22,54,55 while cytoplasmic ERK1/2 without evidence of nuclear localization is typical of degenerating neurons of Alzheimer's disease, 50 and in PD and related models. 25,35 While it is not possible to tell from human autopsy studies whether ERK1/2 regulates mitochondrial turnover or is passively localized to mitochondria and AVs, the current study indicates that activity level-dependent localization of ERK2 to mitochondria is sufficient to induce mitophagy. Moreover, dominant interfering ERK2-KD expression and the MEK inhibitor U0126 prevented both generation and colocalization of ERK2 granules with mitochondria, suppressing 6-OHDA induced mitophagy ( Fig.…”
Section: Discussionmentioning
confidence: 59%
“…The mechanism by which activated ERK2 is enriched in mitochondria is still unknown. While the involvement of mitochondrial reactive oxygen species in redox activation of ERK1/2 suggests a role for in situ phosphorylation, 35,56 the GFP-ERK2 data supports a mechanism involving mitochondrial translocation. Given that phospho-activated ERK represents only a few percent of total cellular ERK, 57 trafficking of this component to a subset of mitochondria may not be detected by standard biochemical fractionation methods.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, recent research suggests that mitochondrial cytochromes could also oxidize HE to a dimeric product [8]. The probe (MitoSOX ™ Red) is being used in the detection and quantitation of mitochondria-generated superoxide [9][10][11]. As mitochondria are enriched with cyt c 3+ (0.1 to 5 mM) [12,13] within the intermembrane compartment, we decided to investigate this reaction in detail.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that 6-OHDA increased the phosphorylation of MAP kinases such as ERK1/2 ( Fig. 6; Kulich et al, 2007), whereas the phosphoylation of Akt was decreased in a dose-dependent manner compared to the control ( Fig. 7; Jiang and Yu, 2005).…”
Section: Discussionmentioning
confidence: 54%